Pola Makan Mempengaruhi Kejadian Sindrom Dispepsia pada Mahasiswa STIKES Graha Medika Kotamobagu - Hairil Akbar (Universitas Widya Gama Mahakam Samarinda, 2020)
Background: Dyspepsia is a set of symptoms in the form of complaints of pain, a feeling of persistent or episodic discomfort in upper stomach accompanied by complaints such as feeling full when eating, satiety, heartburn, bloating, belching, anorexia, nausea, and vomiting. Dyspepsia is one type non contagious disease that occurs not only in Indonesia, but also in the world. Globally there are about 15-40% of the population is dyspepsia sufferers. Every year this complaint concerns 25% of the world's population. In Asia the prevalence of dyspepsia ranges from 8-30%. Objectives: The purpose of this study was to analyze the relationship between eating patterns and the incidence of dyspeptic syndrome in the students of Graha Medika College of Health Sciences, Kotamobagu. Research Metodes: This study applied observational analytic study with cross sectional study approach. The population was all active students of Graha Medika College of Health Sciences, as many as 885 with a total sample of 151 respondents. The sampling technique used was simple random sampling. Data were collected by direct interviews with respondents using a questionnaire and analyzed univariately and bivariately using the chi square test. Results: Statistical test results indicated that there was a relationship between eating patterns (p = 0.006) to the incidence of dyspepsia syndrome in students of Graha Medika College of Health Sciences. Conclusion: There was a relationship between eating pattern and dyspepsia syndrome.